THE EFFECT OF INSTRUCTIONAL, TRANSFORMATIONAL AND SPIRITUAL LEADERSHIP ON ELEMENTARY SCHOOL TEACHERS’ PERFORMANCE AND STUDENTS’ ACHIEVEMENTS - Ahmad Nurabadi; Jusuf Irianto; Ibrahim Bafadal; Juharyanto Juharyanto; Imam Gunawan; Maulana Amirul Adha (LPMPP Universitas Negeri Yogyakarta, 2021)
Persistence for achievement reflected from the willingness and determination of principal to implement quality leadership will facilitate the improvement of teachers’ performance, and the two will be the determinant factors for the students’ ultimate achievement. This study aims at analyzing empirical data on the effect of instructional, transformational and spiritual leadership as independent variables, with school quality as the dependent variable. In addition, the intervening variable is teachers’ performance. This study employed the quantitative approach in which samples of 181 teachers were re taken using the proportional random sampling technique. All data were then analysed using the SEM technique with the AMOS 24 application. The findings show that: (1) there is a direct effect of instructional leadership on teachers’ performance, transformational leadership on teachers’ performance, spiritual leadership on teachers’ performance, instructional leadership on students’ achievement, transformational leadership on students’ achievement, spiritual leadership on students’ achievement, and teachers’ performance on students’ achievement. In addition, (2) there is an indirect effect of instructional leadership on students’ achievement through teachers’ performance, transformational leadership on students’ achievement through teachers’ performance and spiritual leadership on students’ achievement through teachers’ performance.